2000
DOI: 10.1053/ejvs.1999.0954
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining Carotid Flow by Shunting During Carotid Endarterectomy Diminishes the Inflammatory Response Mediating Ischaemic Brain Injury

Abstract: there is a metabolic response to carotid cross-clamping when no shunt is used. However, the clinical significance of this is unclear, since there were no intraoperative strokes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
12

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 26 publications
0
13
0
12
Order By: Relevance
“…Given the subtle nature of the injuries after uncomplicated CEA and the relatively early time of peak serum S100B levels after mild cerebral injuries, it is likely that even earlier S100B sampling (e.g., 2−8 h after CEA) might demonstrate an even stronger correlation between S100B levels and declines in NPMT performance. Also, a recent study of CEA patients reported increased levels of serum markers of inflammation from the jugular bulb ipsilateral to carotid artery clamping (22). We anticipate better correlation between NPMT performance and S100B levels with this more sensitive sampling technique.…”
Section: Discussionmentioning
confidence: 77%
“…Given the subtle nature of the injuries after uncomplicated CEA and the relatively early time of peak serum S100B levels after mild cerebral injuries, it is likely that even earlier S100B sampling (e.g., 2−8 h after CEA) might demonstrate an even stronger correlation between S100B levels and declines in NPMT performance. Also, a recent study of CEA patients reported increased levels of serum markers of inflammation from the jugular bulb ipsilateral to carotid artery clamping (22). We anticipate better correlation between NPMT performance and S100B levels with this more sensitive sampling technique.…”
Section: Discussionmentioning
confidence: 77%
“…PGE 2 is known to directly decrease NK cytotoxicity in vitro (Gatti et al, 1986a; Yakar et al, 2003), through its membrane prostanoid receptors and subsequent elevated intracellular cAMP and activated protein kinase A1 (PKA1) levels (Torgersen et al, 1997a). However, since PGE 2 is released in vivo locally (around the damaged tissue), and its systemic endogenous levels are often not affected (Parsson et al, 2000), it is not clear whether the in vivo effects of PGE 2 depend on a mediating mechanism, such as CORT, which, in the context of surgery, is elevated by PGs (Asoh et al, 1987; Shaashua et al, In press) and by a host of other pro-inflammatory factors (DeKeyser et al, 2000; Turnbull et al, 1994). As will be elaborated below, increased systemic levels of PGs, induced herein by its administration, directly suppressed NKCC in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…For example, we previously reported that systemic administration of PGE 2 that doubled plasma levels of this factor also suppressed in vivo levels of NK cytotoxicity (Yakar et al, 2003). However, it is critical to note that only some studies reported elevated systemic PGE 2 levels after surgery, while other studies reported no such systemic increase (Baxevanis et al, 1994; Buvanendran et al, 2006; Parsson et al, 2000; Vitoratos et al, 1996; Yakar et al, 2003), questioning a direct effect of PGs on NK cytotoxicity. Additionally, although COX inhibitors were shown to reduce post surgical immune suppression (Benish et al, 2008; Faist et al, 1990; Melamed et al, 2005; Yakar et al, 2003), such treatments are also known to reduce CORT levels (Glasner et al, 2010; Shaashua et al, In press).…”
Section: Introductionmentioning
confidence: 99%
“…We attempted to reduce risks of cerebral ischemia by using shunt intraoperatively. 28,29 And mean postoperative neurological complications incidence of patients treated by us declined as time went on ( Figure 6). However, F I G U R E 5 Patients whose nerves were injured or disturbed in operations still suffered neurological complications at follow-up in two groups [Color figure can be viewed at wileyonlinelibrary.com] nerve injuries were hard to be avoided completely in operations, especially for large CBTs.…”
Section: Discussionmentioning
confidence: 98%